2017
DOI: 10.1111/ajpy.12113
|View full text |Cite
|
Sign up to set email alerts
|

Mental health service use and ethnicity: An analysis of service use and time to access treatment by South East Asian‐, Middle Eastern‐, and Australian‐born patients within Sydney, Australia

Abstract: Objective:The current research aimed to assess the association between country of birth and use of a specialised mental health service in Sydney, Australia. Methods: Patient file data were analysed from individuals who accessed the Clinic for Anxiety and Traumatic Stress in Western Sydney between 1996 and 2010. Patients had undergone a clinical assessment and research interview prior to receiving treatment. Data on demographic information and health history were extracted from these files. South East (SE) Asia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…However research shows that migrants, especially those of NESB, experience barriers to accessing treatment, including low mental health literacy, a lack of suitable services and a lack of trust of services [5], as well as the more universal barriers of stigma and cost [6]. In Australia, there is emerging evidence of increasing uptake of face-to-face treatment by migrants [7], but despite this trend, the use of mental health services by many migrant groups remains low.…”
Section: Introductionmentioning
confidence: 99%
“…However research shows that migrants, especially those of NESB, experience barriers to accessing treatment, including low mental health literacy, a lack of suitable services and a lack of trust of services [5], as well as the more universal barriers of stigma and cost [6]. In Australia, there is emerging evidence of increasing uptake of face-to-face treatment by migrants [7], but despite this trend, the use of mental health services by many migrant groups remains low.…”
Section: Introductionmentioning
confidence: 99%
“…A recent Australian systematic review found that these barriers included a lack of accessibility due to cost and availability, acceptability of services due to religious/cultural reasons and affordability [28]. Yet, these di culties were only exacerbated in individuals seeking health care due to a poor understanding of the health care system, discriminatory practices, shame and stigma within communities, and a lack of collaboration within multidisciplinary teams in using culturally appropriate services [29][30][31]. Thus, it is crucial that these barriers are targeted at all levels in order to adequately address the barriers CALD populations may face when accessing healthcare to diagnose and manage autism.…”
Section: Introductionmentioning
confidence: 99%
“…Cultural differences affect treatment access, help seeking, and disclosure of psychological symptoms. Asian Americans may be less likely to seek out mental health treatment and more likely to drop out of therapy (Han & Pong, 2015; S. Lee & Matejkowski, 2012;Logan, Rouen, Wagner, Steel, & Hunt, 2017;Thikeo, Florin, & Ng, 2015). Among older Asian American immigrants (primarily Vietnamese), there may be a greater self-perceived need for mental health care and less access to care (Nguyen, 2011).…”
mentioning
confidence: 99%